Ravitsemuksen, liikunnan ja niiden yhdysvaikutuksen rooli nuorten valtimoterveydessä - Jormanainen, Mika (2024)
A high-energy Western diet and physical inactivity increase the risk of cardiovascular disease. Previous studies have mainly focused on the adult and old-age population. The role of fat quality and the interaction between exercise in arterial health in adolescents has been little studied. This cross-sectional study investigated the relationship between dietary fat quality and physical activity and their combined effect on arterial health in adolescents aged 14–16 years.